Math, asked by Hcjhvkv8610, 1 year ago

If x y z are in gp and tan^-1(x) tan^-1(y) tan^-1(z) are in ap then?

Answers

Answered by RitaNarine
4

Given:

x y z are in GP and

tan^-1(x) tan^-1(y) tan^-1(z) are in AP.

To Find:

The expression which satisfies the above given conditions.

Solution:

  • x, y, z are in GP = > y² = xz - (a )

  • tan^-1(x) tan^-1(y) tan^-1(z) are in AP =  >
  • tan^{-1}x + tan^{-1} z = 2tan^{-1}y
  • tan^{-1}  ( \frac{x+ z}{1 - xz} ) = 2tan^{-1}y
  • \frac{x+z}{1-xz} = tan ( 2tan^{-1}y )

We know ,

  • tan 2x = \frac{2tanx}{1 - tan^{2}x }
  • Therefore, tan(2tan^{-1}y) =  \frac{2tan(tan^{-1}y) }{1 - (tan (tan^{-1} y))^{2} }  =  2y/1-y²
  • \frac{x + z}{1-xz} = 2y/1-y²

We already so that xz = y² .

Therefore,

  • 1 -xz = 1 -y²

Applying this , we get.

  • x + z = 2y

If x y z are in gp and tan^-1(x) tan^-1(y) tan^-1(z) are in ap then x + z =2y

Similar questions